1993
DOI: 10.1177/154193129303700414
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Test of the Kinesis Keyboard

Abstract: A comparative study was conducted to determine the differences in user muscle load, posture, performance and preferences of users for a new technology keyboard (the Kinesis) compared to a standard (traditional) keyboard. The study consisted of requiring 25 test subjects to key text and random letters for two hours on each keyboard. Results demonstrated that hand postures (deviation and extension) and muscle load were better on the Kinesis keyboard. Text entry throughput was greater on the traditional keyboard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Prior literature provides some information in that regard. The average position of the wrist in ulnar deviation during typing has been reported to be between 11°and 25° (Chen et al, 1994;Honan, Serina, Tal, & Rempel, 1995;Nakaseko, Grandjean, Hunting, & Gierer, 1985;Smith & Cronin, 1993;Sommerich & Marras, 1994;Sommerich, Marras, & Parnianpour, 1996); some authors have reported that the amount of ulnar deviation on the left wrist was a few degrees greater than on the right (Hedge & Powers, 1995;Honan, Jacobson, Tal, & Rempel, 1996). Similarly for wrist extension, the average position of the wrist has been reported as between 13°and 33° (Hedge & Powers, 1995;Honan et al, 1995;Honan et al, 1996;Sommerich & Marras, 1994).…”
Section: Introductionmentioning
confidence: 92%
“…Prior literature provides some information in that regard. The average position of the wrist in ulnar deviation during typing has been reported to be between 11°and 25° (Chen et al, 1994;Honan, Serina, Tal, & Rempel, 1995;Nakaseko, Grandjean, Hunting, & Gierer, 1985;Smith & Cronin, 1993;Sommerich & Marras, 1994;Sommerich, Marras, & Parnianpour, 1996); some authors have reported that the amount of ulnar deviation on the left wrist was a few degrees greater than on the right (Hedge & Powers, 1995;Honan, Jacobson, Tal, & Rempel, 1996). Similarly for wrist extension, the average position of the wrist has been reported as between 13°and 33° (Hedge & Powers, 1995;Honan et al, 1995;Honan et al, 1996;Sommerich & Marras, 1994).…”
Section: Introductionmentioning
confidence: 92%
“…(11,14,25) The current study is unique in that dynamic wrist joint postures were measured using an opto-electronic system (Qualisys). With this system, marker positions were transduced in three-dimensional space and dynamic wrist angular positions were calculated from these coordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively high speed, quiet input with large DOF in natural postures are features of the system. EMG signals have been used in keyboard research (Smith and Cronin 1992;Martin et al 1996), although mainly as a rough, relative measurement of force exertion and fatigue.…”
Section: Introductionmentioning
confidence: 99%